Preface to the 10th Anniversary Issue - Lena Lauritsen Bendiksen (Arctic Review on Law and Politics, 2020)
This article is a brief foreword to the ten-year anniversary issue of Arctic Review on Law and Politics with background about the journal written by the dean of the Faculty of Law at UiT The Arctic University of Norway, the journal's sponsor.